Informe de práctica profesional, realizado en la fundación Hogares Claret, para los programas “nueva vida” y “vientos de cambio”, en el periodo comprendido entre enero del 2011 y noviembre del 2011. (2011)
From the following report is the presentation of the activities of a psychology student for ninth and tenth semesters from the academic practice in clinical psychology from a cognitive behavioral approach, between the dates January 27 and October 31 of 2011, Claret Homes Foundation in its programs for youth "Winds of Change" and Adult "New Life" being a population with a particular problem, drug abuse, presenting both the practical functions, such as the results obtained from of them, sustained from theoretical concepts that enhance the production of this report